2017
DOI: 10.1111/jace.14728
|View full text |Cite
|
Sign up to set email alerts
|

Large recoverable energy storage density and low sintering temperature in potassium‐sodium niobate‐based ceramics for multilayer pulsed power capacitors

Abstract: Multilayer pulsed power ceramic capacitors require that dielectric ceramics possess not only large recoverable energy storage density (W rec ) but also low sintering temperature (<950°C) for using the inexpensive metals as the electrodes.However, lead-free bulk ceramics usually show low W rec (<2 J/cm 3 ) and high sintering temperature (>1150°C), limiting their applications in multilayer pulsed power ceramic capacitors. In this work, large W rec (~4.02 J/cm 3 at 400 kV/cm) and low sintering temperature (940°C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 64 publications
0
68
0
Order By: Relevance
“…However, almost all the KNN‐based ferroelectric ceramics examined in previous studies do not satisfy the requirement of both high optical transmittance and high energy storage density. Tables and show the visible optical transparency and energy storage density of most KNN‐based ceramics studied during the 2014‐2017 time period . It was found that transparent ferroelectric ceramics with high energy storage densities have rarely been created in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, almost all the KNN‐based ferroelectric ceramics examined in previous studies do not satisfy the requirement of both high optical transmittance and high energy storage density. Tables and show the visible optical transparency and energy storage density of most KNN‐based ceramics studied during the 2014‐2017 time period . It was found that transparent ferroelectric ceramics with high energy storage densities have rarely been created in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The DBS depends on the grain size and porosity. A smaller grain size and the lower porosity lead to a higher DBS . In addition, relaxor ferroelectrics exhibit a higher P s and lower P r , and thus have a prominent effect on the energy storage density …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This structure leads to a very high volumetric capacitance, and the MLESCCs are suitable for surface‐mount electronics with superior mechanical and thermal properties . Therefore, MLESCCs are considered one of the most promising candidates for energy storage devices and other applications including hybrid electric vehicles and kinetic energy weapons . Generally, the dielectric layers are fabricated with ferroelectric ceramics of high dielectric permittivity, such as barium titanate (BaTiO 3 ), to achieve a high capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…The P max value reaches 39.2 μC/cm 2 with the electric field of 260 kV/cm, the Pr value is up to 13.4 μC/cm 2 ( Figure 7B). 32 In practical applications, the energy storage density (W) and efficiency (η) of ferroelectrics are two important factors to F I G U R E 5 A, Upconversion spectra of the KNLNB:0.01Er transparent ceramic before and after 407 nm irradiation. 31 Under a higher electric field of 260 kV/cm, the polarization intensity of the sample (0.4 mm in thickness) is to be saturated, and no dielectric breakdown appears, showing excellent electric resistance.…”
Section: Ferroelectric and Energy Storage Propertiesmentioning
confidence: 99%